Freedom vs necessity in international relations : human-centred approaches to security and development - Chandler, David, 1962- (Zed Books, 2013)
The last two decades have seen the rise to dominance of human-centred understandings of the world. Indeed, it is now rare to read any analysis of insecurity, conflict or development which does not discuss the need to empower local individuals or communities. As David Chandler argues in this path-breaking book, human-centred approaches have limited rather than expanded the transformative possibilities available to us, and if real change is to be achieved then a radical re-think is required.